Bee Venom—A Potential Complementary Medicine Candidate for SARS-CoV-2 Infections - Kasozi, Keneth Iceland; Niedbała, Gniewko; Alqarni, Mohammed; Zirintunda, Gerald; Ssempijja, Fred; Musinguzi, Simon Peter; Usman, Ibe Michael; Matama, Kevin; Hetta, Helal F.; Mbiydzenyuy, Ngala Elvis; Batiha, Gaber El-Saber; Beshbishy, Amany Magdy; et al. (Frontiers in Public Health, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is characterized by severe cytokine storm syndrome following inflammation. SARS-CoV-2 directly interacts with the angiotensin-converting enzyme 2 (ACE-2) receptors in the human body. Complementary therapies, that impact onthe expression of the IgE and IgG antibodies, including the administration of bee venom (BV), have efficacy in the management of arthritis and Parkinson's disease. A recent epidemiological study in China showed that local beekeeper’sbeekeepers have a level of immunity against SARS-CoV-2 with and without previous exposure to virus. BV anti-inflammatory properties are associated with melittin and phospholipase A2 (PLA2), both of which show activity against enveloped and non-enveloped viruses, including H1N1 and HIV, with activity mediated through antagonist activity against interleukin-6 (IL-6), IL-8, interferon-γ (IFN-γ) and tumour necrosis factor-α (TNF-α). Melittin is associated with underexpression the underexpression of proinflammatory cytokines;, including nuclear factor-kappa B (NF-κB), extracellular signal-regulated kinases (ERK1/2) and protein kinase Akt. BV therapy also involves group III secretory phospholipase A2 in the management of respiratory and neurological diseases. BV activation of the cellular and humoral immune systems should be explored for the application of complementary medicine for the management of SARS-CoV-2 infections. BV “vaccination” is used to immunize against cytomegalovirus and can suppress metastases through the PLA2 and phosphatidylinositol-(3,4)-bisphosphate pathways. That BV shows efficacy for the HIV and H1NI offers opportunity as a candidate for complementary therapy for protection against SARS-CoV-2.